First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Small Phytoplankton Community Composition Cycles Annually With a Coastal Bloom - Bethany L. F. Stevens; Rebecca J. Gast; Emily E. Peacock; Yogesh A. Girdhar; Michael G. Neubert; Heidi M. Sosik (Environmental Microbiology, 2025)
Small photosynthetic eukaryotes are a productive and dynamic component of marine planktonic communities. Here, we investigate how seasonal changes in the abundance of these primary producers relate to changes in their community composition at a coastal site on the Northeast US Shelf. We present a 9‐year time series of 18S rRNA sequencing data and identify gradual transitions within the pico‐ and nanoplankton community that occur repeatedly over the annual cycle. We compare these compositional changes to concurrent high‐resolution in situ flow cytometry measurements of eukaryotic phytoplankton abundance and division rate. We find that the Chlorophyta contribute a large proportion of the sequences in our samples and drive much of the seasonal variability within the small phytoplankton community. Across the time series, Bathycoccus , Micromonas and Picochlorum are the dominant genera, with the first being present year‐round, while Micromonas bravo and Picochlorum are representative of the summer community. We also find a strong winter Phaeocystis signal which might be leading to flow cytometry measurements of relatively large cells in the early spring. Our results provide fundamental knowledge of the taxonomic composition of the phytoplankton community on the Northeast US Shelf, improving our understanding of the region's diversity and compositional variability over time.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Integrative phylogenetic, phylogeographic and morphological characterisation of the Unio crassus species complex reveals cryptic diversity with important conservation implications - M. Lopes-Lima; J. Geist; S. Egg; L. Beran; A. Bikashvili; B. Van Bocxlaer; A.E. Bogan; I.N. Bolotov; O.A. Chelpanovskaya; K. Douda; V. Fernandes; A. Gomes-dos-Santos; et al. (Molecular Phylogenetics and Evolution, 2024)

Distinct responses to warming within picoplankton communities across an environmental gradient - Bethany L. F. Stevens; Emily E. Peacock; E. Taylor Crockford; Alexi Shalapyonok; Michael G. Neubert; Heidi M. Sosik (Global Change Biology, 2024)
Picophytoplankton are a ubiquitous component of marine plankton communities and are expected to be favored by global increases in seawater temperature and stratification associated with climate change. Eukaryotic and prokaryotic picophytoplankton have distinct ecology, and global models predict that the two groups will respond differently to future climate scenarios. At a nearshore observatory on the Northeast US Shelf, however, decades of year‐round monitoring have shown these two groups to be highly synchronized in their responses to environmental variability. To reconcile the differences between regional and global predictions for picophytoplankton dynamics, we here investigate the picophytoplankton community across the continental shelf gradient from the nearshore observatory to the continental slope. We analyze flow cytometry data from 22 research cruises, comparing the response of picoeukaryote and Synechococcus communities to environmental variability across time and space. We find that the mechanisms controlling picophytoplankton abundance differ across taxa, season, and distance from shore. Like the prokaryote, Synechococcus , picoeukaryote division rates are limited nearshore by low temperatures in winter and spring, and higher temperatures offshore lead to an earlier spring bloom. Unlike Synechococcus , picoeukaryote concentration in summer decreases dramatically in offshore surface waters and exhibits deeper subsurface maxima. The offshore picoeukaryote community appears to be nutrient limited in the summer and subject to much greater loss rates than Synechococcus . This work both produces and demonstrates the necessity of taxon‐ and site‐specific knowledge for accurately predicting the responses of picophytoplankton to ongoing environmental change.

Localized Native American impacts on past forest composition across a regional extent in north‐eastern United States - Stephen J. Tulowiecki; Emma R. Ranney; Emily M. Keenan; Gabrielle M. Neubert; Marcie L. Hogan (Journal of Biogeography, 2022)
Aim Researchers have debated impacts of past Native American land use on forests including upon tree species composition in north‐eastern United States (US), with estimates of impacts ranging from local to regional extent. This study examines tree relative abundances to assess whether Native Americans influenced geographic distributions prior to Euro‐American settlement. Location North‐eastern United States (approx. 420,000 km 2 ). Taxon Ash ( Fraxinus spp.), basswood ( Tilia americana ), beech ( Fagus grandifolia ), birch ( Betula spp.), cherry ( Prunus spp.), chestnut ( Castanea dentata ), dogwood ( Cornus spp.), elm ( Ulmus spp.), fir ( Abies balsamea ), hemlock ( Tsuga canadensis ), hickory ( Carya spp.), ironwood ( Carpinus caroliniana and Ostrya virginiana ), maple ( Acer spp.), oak ( Quercus spp.), pine ( Pinus spp.), spruce ( Picea spp.), tamarack ( Larix laricina ) and walnut ( Juglans spp.), Methods We used boosted regression trees to model abundance patterns and to assess the importance of distance‐based proxies of Native American land use versus environmental variables. We trained models that included and excluded distance‐based proxies. Abundance estimates from original land survey records (1650–1850 CE) were acquired for taxa at 8 km spatial resolution, and related to Native American settlement locations (1500–1800 CE) and 27 environmental variables. Results When evaluated upon test data, regional‐scale models of relative abundance that included distance‐based proxies performed only slightly better than models that excluded them, with mean improvements in RMSE of 0.1 percentage points. Models suggest that Native American land use modestly altered the relative abundance of taxa locally, extending no more than 50 km from settlement. Models also suggest slight increases near settlement of a few percentage points in relative abundance for fire‐tolerant and/or dietary taxa (e.g. oak, hickory and pine), and for early‐successional taxa (e.g. ash). Main conclusions Past Native American land use had no detectable effect on forest composition across a regional extent, but increased the abundance of fire‐tolerant, shade‐intolerant and nut‐producing trees locally.

The conservation status of the world’s freshwater molluscs - Monika Böhm; Nadia I. Dewhurst-Richman; Mary Seddon; Sophie E. H. Ledger; Christian Albrecht; David Allen; Arthur E. Bogan; Jay Cordeiro; Kevin S. Cummings; Annabelle Cuttelod; Gustavo Darrigran; Will Darwall; et al. (Hydrobiologia, 2021)

The extreme capsule fiber complex in humans and macaque monkeys: a comparative diffusion MRI tractography study - Rogier B. Mars; Sean Foxley; Lennart Verhagen; Saad Jbabdi; Jérôme Sallet; MaryAnn P. Noonan; Franz-Xaver Neubert; Jesper L. Andersson; Paula L. Croxson; Robin I. M. Dunbar; Alexandre A. Khrapitchev; Nicola R. Sibson; et al. (Brain Structure and Function, 2016)

Seven years of recent European net terrestrial carbon dioxide exchange constrained by atmospheric observations - W. PETERS; M. C. KROL; G. R. Van Der WERF; S. HOUWELING; C. D. JONES; J. HUGHES; K. SCHAEFER; K. A. MASARIE; A. R. JACOBSON; J. B. MILLER; C. H. CHO; M. RAMONET; et al. (Global Change Biology, 2010)
We present an estimate of net ecosystem exchange (NEE) of CO 2 in Europe for the years 2001–2007. It is derived with a data assimilation that uses a large set of atmospheric CO 2 mole fraction observations (∼70 000) to guide relatively simple descriptions of terrestrial and oceanic net exchange, while fossil fuel and fire emissions are prescribed. Weekly terrestrial sources and sinks are optimized (i.e., a flux inversion) for a set of 18 large ecosystems across Europe in which prescribed climate, weather, and surface characteristics introduce finer scale gradients. We find that the terrestrial biosphere in Europe absorbed a net average of −165 Tg C yr −1 over the period considered. This uptake is predominantly in non‐EU countries, and is found in the northern coniferous (−94 Tg C yr −1 ) and mixed forests (−30 Tg C yr −1 ) as well as the forest/field complexes of eastern Europe (−85 Tg C yr −1 ). An optimistic uncertainty estimate derived using three biosphere models suggests the uptake to be in a range of −122 to −258 Tg C yr −1 , while a more conservative estimate derived from the a‐posteriori covariance estimates is −165±437 Tg C yr −1 . Note, however, that uncertainties are hard to estimate given the nature of the system and are likely to be significantly larger than this. Interannual variability in NEE includes a reduction in uptake due to the 2003 drought followed by 3 years of more than average uptake. The largest anomaly of NEE occurred in 2005 concurrent with increased seasonal cycles of observed CO 2 . We speculate these changes to result from the strong negative phase of the North Atlantic Oscillation in 2005 that lead to favorable summer growth conditions, and altered horizontal and vertical mixing in the atmosphere. All our results are available through http://www.carbontracker.eu

Analysis of vaccine-virus-associated rabies cases in red foxes (Vulpes vulpes) after oral rabies vaccination campaigns in Germany and Austria - Thomas Müller; H.-J. Bätza; A. Beckert; C. Bunzenthal; J. H. Cox; C. M. Freuling; A. R. Fooks; J. Frost; L. Geue; A. Hoeflechner; D. Marston; A. Neubert; et al. (Archives of Virology, 2009)